2017
DOI: 10.1038/s41598-017-02321-y
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual house dust mite immunotherapy has no impact on decrease of circulating erythrocytes upon airway allergen challenge in allergic rhinitis

Abstract: House dust mite (HDM) allergy is a predominant cause for perennial allergic rhinitis (AR) in Europe. We recently reported that circulating erythrocyte numbers decrease after airway allergen challenge in a murine asthma model and in grass-pollen sensitized AR subjects. Consequently, we aimed to evaluate these findings in HDM sensitized AR subjects and the influence of preceding allergen immunotherapy. Seventy-seven (age 26.8 ± 7.3 years; 54.5% female) HDM-allergic rhinitis subjects previously enrolled in a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…Recent publications by G. Jordakieva and coauthors revealed that one of the obscure phenomena, when a causally significant allergen is introduced into a sensitized macroorganism, is a decrease in hemoglobin and erythrocytes [9,10]. However, we failed to find any reports on the characteristic hematological features in the patients with hypersensitivity reactions in clinically manifested syndromes of skin damages and/or anaphylaxis.…”
Section: Introductioncontrasting
confidence: 62%
“…Recent publications by G. Jordakieva and coauthors revealed that one of the obscure phenomena, when a causally significant allergen is introduced into a sensitized macroorganism, is a decrease in hemoglobin and erythrocytes [9,10]. However, we failed to find any reports on the characteristic hematological features in the patients with hypersensitivity reactions in clinically manifested syndromes of skin damages and/or anaphylaxis.…”
Section: Introductioncontrasting
confidence: 62%
“…Serum PF-4 and β-TG levels in HDM AR patients appear to be comparable to those in healthy controls [ 125 ]. Incidentally, we found a significant increase in circulating thrombocytes after 2 h of continuous allergen challenge compared to baseline values [ 8 , 9 ]; however, 4 h after allergen challenge, no significant changes in circulating thrombocyte numbers were observed (data not published). During AIT in grass pollen AR, no changes in platelet activation marker β-TG levels were observed in plasma, even with during administration of the highest vaccine dose [ 126 ].…”
Section: Blood Cells In Armentioning
confidence: 70%
“…Blood neutrophils, particularly segmented neutrophils, increase upon allergen challenge [ 8 , 9 ] and show altered functions in AR. For example, circulating blood neutrophils from AR patients produced more LTB2 after stimulation with calcium ionophore than controls.…”
Section: Blood Cells In Armentioning
confidence: 99%
See 1 more Smart Citation
“…HDM are therefore carefully considered with respect to the management and treatment of atopic diseases [9, 10]. Moreover, HDM extracts are frequently used in experimental models in research focused on allergy and atopy [11, 12]. …”
Section: Introductionmentioning
confidence: 99%